The relationship between behavior problems, gender, special education status and school performance in the early grades of school - Liukkonen, Taru (2017)
Liukkonen, Taru. 2017. The relationship between behavior problems, gender, special education status and school performance in the early grades of school. Master’s thesis in special education. University of Jyväskylä. Department of Education and Psychology. 41 pages. The purpose of this master’s thesis was to find out whether there are changes in the average level of behavior problems of pupils from 1st to 2nd grade and wheth-er gender or receiving part-time special education is related to the average level or possible change in behavior problems. Furthermore this study tested wheth-er behavior problems in the 1st grade predict the school performance in reading, writing and mathematics in the 2nd grade. The data used in the study was collected as a part of the Eastern Finland special education development project (ISKE). The data was collected years 2010-2012 from six municipalities in Eastern Finland. 30 schools and 57 classes from these municipalities participated in the research. A total of 311 1st grade pupils were included in this study and followed through the 2nd grade. There was no change in the level of behavior problems from 1st to 2nd grade. There were no differences in the trend of behavior problems between genders or between students who were receiving or not receiving part time special edu-cation. However, boys had on the average more behavior problems than girls. The behavior problems in the 1st grade predicted lower school performance in writing on the 2nd grade, but not the performance in reading or mathematics on the 2nd grade. It was concluded that, the known negative effects of behavior problems can be seen already in the very beginning of school. The result is consistent with earlier studies, showing negative consequences for older pupils. These findings highlight the importance of supporting pupils expressing behavior problems already in the beginning of school before the problems escalate and start affect-ing eg. School performance. The role of universal support (Tier 1) is crucial in this regard. In the future it is important to study and develop proactive ways to support behavior and behavior management in schools and classrooms.